Mobile agent based multi-layer security framework for cloud data centers - Uddin, Mueen; Memon, Jamshed; Alsaqour, Raed A.; Shah, Asadullah; Abdul Rozan, Mohd Zaidi (Informatics (India) Ltd., 2015)
Objective:This paper proposes a new mobile agent based cloud security framework comprising four different security and authentication layers to establish the trust relationship between two entities before using cloud services. Methods/Analysis:The proposed framework is divided into four layers with each performing authentication, verification and integrity at different levels of communication between entities. An algorithm is used to check and analyze the validity and functionality of each layer. Mobile agents are used as main components for performing different tasks assigned and requested by clients from cloud service providers. Findings:The framework uses authenticated mobile agents from both client and cloud server provider to perform the task on behalf of users to establish trustworthy computing relationship. This makes the whole process transparent and clear according to users and cloud service providers' perspective. The proposed framework effectively ensures privacy and security of clients data and gives control to client over his data using the security agents. Conclusion and Application: The main contribution of this paper is undoubtedly the agreement of trustworthy relationship between two entities to agree on security service level agreements to dynamically configure and add mobile agents on virtual machine handled by task managers in their respective mobile agent platform